2015
DOI: 10.1093/icesjms/fsv030
|View full text |Cite
|
Sign up to set email alerts
|

Video capture of crustacean fisheries data as an alternative to on-board observers

Abstract: For EU member states to meet the requirements of the Marine Strategy Framework Directive and the reformed Common Fisheries Policy, it will be necessary to improve data collection related to many fisheries that are at present subject to relatively little monitoring or scientific research. This study evaluated the use of on-board camera systems to collect data from Cancer pagurus and Homarus gammarus fisheries. We evaluated the reliability of the hardware and its ability to collect images of sufficient accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…This level of error is comparable to that observed by Hold et al (2015) who used a fiducial marker to estimate carapace size in crab and lobster where the mean differences between estimated and actual lengths were 0.1 % and 0.6 % respectively. Similar mean differences have been reported when using paired lasers (Deakos 2010, 0.4 % in Manta alfredi), or multi-camera systems (Rosen et al 2013 1.0 % in 3 fusiform fish species).…”
Section: Distortion Correctionsupporting
confidence: 81%
See 3 more Smart Citations
“…This level of error is comparable to that observed by Hold et al (2015) who used a fiducial marker to estimate carapace size in crab and lobster where the mean differences between estimated and actual lengths were 0.1 % and 0.6 % respectively. Similar mean differences have been reported when using paired lasers (Deakos 2010, 0.4 % in Manta alfredi), or multi-camera systems (Rosen et al 2013 1.0 % in 3 fusiform fish species).…”
Section: Distortion Correctionsupporting
confidence: 81%
“…In contrast, OpenCV and Python offer greater platform agnosticism, with support across MS Windows, Mac OS, Android, Linux and other platforms. Hold et al (2015) found that radial distortion was limited by ensuring the subject was centred in the FoV (also see Rodgers et al, 2017). The parallax effect was empirically controlled with a 2 nd order linear model with FoV as a predictor.…”
Section: Distortion Correctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have been carried out to measure the effectiveness of REM systems at monitoring industrial fishing activities, including target catch (Ames et al, 2007;Hold et al, 2015;Kindt-Larsen et al, 2011;Stanley et al, 2009) (c) Fig. 1.…”
Section: Introductionmentioning
confidence: 99%